Shear behavior of greenschist along foliation plane considering anisotropy - Zhang, Qingzhao (2021)
The shear behavior of rock mass along its structural plane, i.e., joint, bedding plane, and foliation plane, plays a key role in determining rock strength which is highly anisotropic. The shear behavior along the foliation plane is rarely addressed from engineering geology point of view in the effect of anisotropy of on the shear behavior along foliation plane, not to mention the effect of anisotropy. In this study, the direct shear behavior of greenschist along the foliation plane is investigated using both intact and sheared greenschist samples. Identical concrete replicas for the sheared greenschist samples are prepared using 3D scanning and printing, in this study, and sheared in four directions, i.e., 0°, 90°, 180°, and 270°, under four normal stresses (σ n / σ c = 0.1 , 0.2 , 0.3 , 0.4). The intact greenschist samples show significantly higher shear strength compared to the sheared samples due to the bonding strength along foliation plane. The shear behavior of greenschist along foliation plane is anisotropic due to the 3D roughness of foliation plane, and the anisotropic behavior diminishes as the normal stress increases. Moreover, the replicas of sheared greenschist samples shows same shear strength as the sheared greenschist samples, thus suggesting that the concrete is suitable for simulating greenschist shear behavior, including the peak shear strength, residual shear strength and stiffness, which also hints that the shear behavior of the sheared greenschist is dramatically controlled by surface roughness of the joint rather than rack by comparing the results of the shear greenschist with concrete replicas.